2013
DOI: 10.1038/srep02426
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient and robust cathode materials for low-temperature solid oxide fuel cells: PrBa0.5Sr0.5Co2−xFexO5+δ

Abstract: Solid oxide fuel cells (SOFC) are the cleanest, most efficient, and cost-effective option for direct conversion to electricity of a wide variety of fuels. While significant progress has been made in anode materials with enhanced tolerance to coking and contaminant poisoning, cathodic polarization still contributes considerably to energy loss, more so at lower operating temperatures. Here we report a synergistic effect of co-doping in a cation-ordered double-perovskite material, PrBa0.5Sr0.5Co2−xFexO5+δ, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
230
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 328 publications
(236 citation statements)
references
References 35 publications
5
230
1
Order By: Relevance
“…Lowering the operating temperature of SOFCs to intermediate range (500-800 C) offers many advantages such as prolonged lifetime, flexible choice of cell materials, shortened start-up time, reduced materials cost which might open new opportunity for SOFCs applications on auxiliary power units for vehicles, remote power supplies, portable electronic appliance powering, etc [3][4][5][6][7]. However, the conducting species encounter higher activation barriers at lower temperature, and the oxygen reduction reaction (ORR) kinetics occurred at cathode side became the primary challenge to achieve high performance of SOFCs at reduced operation temperature [4,8].…”
Section: Introductionmentioning
confidence: 99%
“…Lowering the operating temperature of SOFCs to intermediate range (500-800 C) offers many advantages such as prolonged lifetime, flexible choice of cell materials, shortened start-up time, reduced materials cost which might open new opportunity for SOFCs applications on auxiliary power units for vehicles, remote power supplies, portable electronic appliance powering, etc [3][4][5][6][7]. However, the conducting species encounter higher activation barriers at lower temperature, and the oxygen reduction reaction (ORR) kinetics occurred at cathode side became the primary challenge to achieve high performance of SOFCs at reduced operation temperature [4,8].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the numerous studies on each part (anode, cathode and electrolyte), high-performance LT-SOFCs, especially ceriabased LT-SOFCs [35][36][37][38] , have been rarely reported with few exceptions: Wachsman et al 4 39 and Choi et al 40 and Park et al 41 recently reported over 1.2 W cm À 2 at 550°C in a cell with a PrBa 0.5 Sr 0.5 Co 1.5 Fe 0.5 O 5 þ d (PBSCF05) cathode. Here, we report an original cell design, the core/shell-fibre-structured BSCF-GDC cathode | thin GDC electrolyte | nanocomposite Ni-GDC AFL | Ni-GDC anode fuel cell to achieve high and stable performance GDC-based LT-SOFCs.…”
mentioning
confidence: 99%
“…1,2 However, the low operating temperature gives rise to poor activity for the oxygen reduction reaction (ORR) at the cathode. Accordingly, the development of cathode materials with high electro-catalytic activity and excellent durability is necessary for commercialization of IT-SOFCs.…”
mentioning
confidence: 99%